Analisa Rantai Pasok (Supply Chain) Bahan Baku pada Industri Kuliner Bebek dan Ayam Goreng (Studi Kasus : Depot Bebek dan Ayam Goreng Pak Qomar) - Zaidi, Abdul Hamid; Murnawan, Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of the research is to determine the flow of the duck supply chain which includes product flow, financial flow and information flow from duck breeders to the restaurant